Development of the Socioeconomic Index for Rakyat’s (SEIR) well-being: a holistic approach - Mohamed Isa, Zuraidah; Ali, Norhidayah; Ibrahim, Dahlia; Anuar, Azyyati; Abu Bakar, Suhaida; Othman, Nor Salwati (Universiti Teknologi MARA, Kedah, 2023)
The COVID-19 pandemic has had a significant impact on the socioeconomic status of the population in Malaysia. The government’s response to the pandemic, including the movement control order (MCO), has led to widespread job losses and income reductions. This has had a negative impact on the dimensions of socioeconomic status, including income, savings, occupation, food supply, health, personal safety, emotions, spirituality, and productivity. A number of researchers have studied the socioeconomic impact of the COVID-19 pandemic, but there is a need for a comprehensive measure of the impact. The Socioeconomic Index for Rakyat (SEIR) is a comprehensive index that measures the impact of the pandemic on the population’s socioeconomic conditions. SEIR is based on the following dimensions: income, savings, occupation, food supply, health, medical care, emotional well-being, religion, spirituality, education, housing, networking, productivity, and personal safety. SEIR is a valuable tool for policymakers and other stakeholders to track the impact of the pandemic on the population’s socioeconomic conditions and to develop strategies to mitigate the impact. While SEIR is still under development, it has the potential to be a valuable tool for policymakers and other stakeholders. The development of SEIR is an important step towards understanding the full impact of the COVID-19 pandemic on the socioeconomic status of Malaysia’s population.